Playing to develop / increase spoken interaction - Inácio, Maria Salomé Batista Rodrigues (2017)
With the intention of increasing the focus on communication and finding motivating speaking activities to encourage students to interact in the foreign language classroom with their peers and teacher, this research project investigated whether playful activities, such as songs, games and role-play activities can help primary level students improve their speaking skills. Playful activities were used to promote spoken interaction among students in a third year class, engaging and motivating students to make them talk in English. In order to collect data to investigate the development of students’ speaking skills, the research tools used were questionnaires, a teacher reflective journal and group interviews. Children’s motivation to learn was always regarded, since it is crucial to engage students in new and diverse activities and tasks, helping them overcome their learning difficulties. Students’ reaction to these speaking activities revealed great enthusiasm and willingness to overcome the challenges that these presented. Their progress as foreign language speakers was monitored during the first school term, and their positive attitude towards speaking activities showed that these kept them motivated and engaged in the lessons. The notion that they could improve their skills playing in English was confirmed during the group interviews, as students justified that they could learn more and have fun at the same time.